Role of asparagine biosynthesis pathway in Siniperca chuatsi rhabdovirus proliferation - Li, Fangying; Fu, Xiaozhe; Luo, Xia; Lin, Qiang; Liang, Hongru; Niu, Yinjie; Liu, Lihui; Li, Ningqiu (Frontiers in Microbiology, 2023)
Viruses are non-living organisms that rely on host cellular metabolism to complete their life cycle. Siniperca chuatsi rhabdovirus (SCRV) has caused huge economic losses to the Chinese perch (Siniperca chuatsi) industry worldwide. SCRV replication is dependent on the cellular glutamine metabolism, while aspartate metabolism plays an important role in viral proliferation in glutamine deficiency. Herein, we investigated roles of asparagine metabolism in SCRV proliferation. Results showed that SCRV infection up-regulated the expression of key enzymes in the aspartate metabolic pathway in CPB cells. And the key enzymes of malate-aspartic acid shuttle pathway up-regulated during the virus invasion phase, and key enzymes of the asparagine biosynthesis pathway up-regulated during the viral replication and release phase. When asparagine was added to the depleted medium, the SCRV copy number restored to 90% of those in replete medium, showing that asparagine and glutamine completely rescue the replication of SCRV. Moreover, inhibition of the aspartate- malate shuttle pathway and knockdown of the expression of key enzymes in the asparagine biosynthesis pathway significantly reduced SCRV production, indicating that the aspartic acid metabolic pathway was required to the replication and proliferation of SCRV. Above results provided references for elucidating pathogenic mechanism of SCRV by regulation of aspartate metabolism.